2014
DOI: 10.1016/j.healun.2013.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Liver cirrhosis in Fontan patients does not affect 1-year post-heart transplant mortality or markers of liver function

Abstract: Background Liver cirrhosis is recognized with long-term follow-up of patients after the Fontan procedure. The effect of liver cirrhosis on the use of heart transplant (HT) and on post-HT outcomes is unknown. Methods We reviewed Fontan patients evaluated for HT from 2004 to 2012 with hepatic computed tomography (CT) imaging, classified as normal, non-cirrhotic changes, or cirrhosis. The primary outcome was 1-year all-cause mortality, and the secondary outcome was differences in serial post-HT liver evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 19 publications
2
47
0
Order By: Relevance
“…Another recent study found no association between hepatic imaging and post-transplant outcomes in Fontan patients. 30 Therefore, we recommend considering histopathologic findings as one part of the greater picture when evaluating subjects for transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study found no association between hepatic imaging and post-transplant outcomes in Fontan patients. 30 Therefore, we recommend considering histopathologic findings as one part of the greater picture when evaluating subjects for transplant.…”
Section: Discussionmentioning
confidence: 99%
“…In multivariate analysis, only the time since initial Fontan procedure was associated with hepatic complications. Importantly, Simpson et al 151 found in a small study of Fontan patients (mean age, 13 years) that computed tomography evidence of liver cirrhosis did not predict 1-year mortality after HTx. They did not systematically assess MELD scores, histology, or HVPG.…”
Section: Systemic Venous Anomalies In Patients With Situs Inversus Ormentioning
confidence: 97%
“…100,101 The impacts of portal fibrosis and cirrhosis on outcomes after transplantation are under investigation, with a few patients undergoing heart and liver transplantation when advanced cirrhosis is present. [102][103][104] The type of congenital heart disease also affects survival after transplantation. Patients who have undergone the Fontan procedure have a higher posttransplantation mortality than patients with other types of congenital heart disease, with one series reporting a hazard ratio of 8 for early mortality.…”
Section: Risk Factors For Mortality Unique To Patients With Congenitamentioning
confidence: 99%